Bibliometrik Analisis: Brand Awareness Program Studi Diploma 3 Pada Database Scopus - Bani Nurhakim; Dadang Sudrajat (Prosiding SISFOTEK, 2024)
This research aims to analyze the factors influencing brand awareness in the Diploma 3 program and to develop effective marketing strategies to enhance that awareness. The background of this study is based on the importance of brand awareness in influencing prospective students' decisions and public perception of the quality and reputation of educational institutions. This research employs survey and interview methods involving students, prospective students, and marketing staff from several higher education institutions in Indonesia. The data obtained were analyzed using statistical methods to identify the main factors affecting brand awareness. The results indicate that digital marketing and social media marketing play a significant role in increasing brand awareness of the Diploma 3 program. Consistent, innovative, and effective marketing strategies through social media have been proven to enhance recognition and appeal of the study program in the eyes of prospective students. This research makes an important contribution to the development of educational marketing strategies and offers new approaches to enhancing brand awareness of the Diploma 3 program. Thus, the results of this study are expected to assist educational institutions in increasing enrollment and retaining students by improving effective brand awareness